Wed wabbit - Evans, Lissa ca. 20. Jh (Scholastic Inc., 2018)
You're called Fidge and you're nearly 11. You've been hurled into a strange world. You have three companions: two are unbelievably weird and the third is your awful cousin Graham. You have to solve a series of nearly impossible clues. You need to deal with a cruel dictator and three thousand Wimbley Woos (yes, you read that sentence correctly). And the whole situation - the whole, entire thing - is your fault